2021
DOI: 10.1371/journal.pone.0249638
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementation of oral rehydration therapy in low- and middle-income countries: A systematic review

Abstract: Background Oral rehydration therapy (ORT) is an effective and cheap treatment for diarrheal disease; globally, one of the leading causes of death in children under five. The World Health Organization launched a global campaign to improve ORT coverage in 1978, with activities such as educational campaigns, training health workers and the creation of designate programming. Despite these efforts, ORT coverage remains relatively low. The objective of this systematic review is to identify the barriers and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…However, several studies reported that mothers and other caregivers in Pakistan still treat diarrhea in children with home remedies or self-prescribed medication, including antibiotics, and only one third of caregivers manage pediatric diarrhea using ORS (Aftab et al, 2018 ; Khan et al, 2019 ). One of the main reasons for these findings is the inaccessibility and non-affordability of ORS which constitutes a major barrier for ORS therapy in Pakistan, especially in socioeconomically deprived areas (Ezezika et al, 2021 ). Thus, efforts should be made to increase the accessibility and affordability of ORS for example by providing subsidiary in ORS pricing.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that mothers and other caregivers in Pakistan still treat diarrhea in children with home remedies or self-prescribed medication, including antibiotics, and only one third of caregivers manage pediatric diarrhea using ORS (Aftab et al, 2018 ; Khan et al, 2019 ). One of the main reasons for these findings is the inaccessibility and non-affordability of ORS which constitutes a major barrier for ORS therapy in Pakistan, especially in socioeconomically deprived areas (Ezezika et al, 2021 ). Thus, efforts should be made to increase the accessibility and affordability of ORS for example by providing subsidiary in ORS pricing.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). In addition, there is a need to strengthen measures for mortality deterrence by proper management of dehydration through effective delivery of oral rehydration solution and zinc supplementation services by primary health care facilities ( APHA 2018 ; Ezezika et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, introducing vaccines and sustaining the gains from water, sanitation, and hygiene as well as child nutrition programs can help prevent infections in the future (Riddle et al 2018;Troeger et al 2020). In addition, there is a need to strengthen measures for mortality deterrence by proper management of dehydration through effective delivery of oral rehydration solution and zinc supplementation services by primary health care facilities (APHA 2018;Ezezika et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the selection of a determinant framework (CFIR) is a potential limitation as such frameworks have been criticized for their inadequacy in addressing causal mechanisms or how change takes place [49]. However, the use of the CFIR allowed the findings to be placed in the context of the wider implementation research literature and has been successfully applied in similar systematic reviews [50,51]. Finally, we extracted only qualitative-oriented data from each eligible article; thus, other significant results might have been overlooked.…”
Section: Strengths and Limitationsmentioning
confidence: 99%